How Aware Are Migraineurs of Their Triggers?. Issue 5 (27th March 2013) - Baldacci, Filippo; Vedovello, Marcella; Ulivi, Martina; Vergallo, Andrea; Poletti, Michele; Borelli, Paolo; Nuti, Angelo; Bonuccelli, Ubaldo
<x xml:space="preserve">Abstract</x> Background Broad discrepancies in the number of migraine triggers have been reported in several studies. Migraineurs do not seem to recognize easily headache triggers in clinical practice. Objective To evaluate how aware migraineurs are about their headache triggers. Materials and methods We recruited 120 consecutive migraineurs. Each patient was first asked to report spontaneously any migraine trigger. Subsequently, the patient selected from a list of commonly known triggers. Results Ninety‐seven patients (72.5%) spontaneously reported at least 1 migraine trigger, and 120 patients (100%) reported at least 1 migraine trigger selecting from a specific list of precipitants. The mean number of spontaneously identified triggers was 1.5 (±1.5), and the total number of triggers identified was 7.20 (±3.9). Conclusions A relevant discrepancy between the number of spontaneously recognized triggers and the total number of triggers was found. This may suggest that migraineurs display poor awareness about headache triggers.